Balance Impairments after Brachial Plexus Injury as Assessed through Clinical and Posturographic Evaluation - Souza, Lidiane; Lemos, Thiago; Silva, Débora C.; de Oliveira, José M.; Guedes Corrêa, José F.; Tavares, Paulo L.; Oliveira, Laura A.; Rodrigues, Erika C.; Vargas, Claudia D. (Frontiers in Human Neuroscience, 2016)
Objective: To investigate whether a sensorimotor deficit of the upper limb following a brachial plexus injury (BPI) affects the upright balance. Design: Eleven patients with a unilateral BPI and 11 healthy subjects were recruited. The balance assessment includes the Berg Balance Scale (BBS), the number of feet touches on the ground while performing a 60s single-leg stance and posturographic assessment (eyes open and feet placed hip-width apart during a single 60s trial). The body weight distribution (BWD) between the legs was estimated from the center of pressure (COP) lateral position. The COP variability was quantified in the anterior-posterior and lateral directions. Results: BPI patients presented lower BBS scores (p=0.048) and a higher frequency of feet touches during the single-leg stance (p=0.042) compared with those of the healthy subjects. An asymmetric BWD toward the side opposite the affected arm was showed by 73% of BPI patients. Finally, higher COP variability was observed in BPI patients compared with healthy subjects for anterior-posterior (p=0.020), but not for lateral direction (p=0.818). Conclusions: This study demonstrates that upper limb sensorimotor deficits following BPI affect body balance, serving as a warning for the clinical community about the need to prevent and treat the secondary outcomes of this condition.